PENGARUH APOTEK HIDUP TERHADAP PENGENALAN SAINS ANAK USIA 5-6 TAHUN DI TK ABA 066 BROMO MEDAN - Rahmi Wardah Ningsih; Anita Yus; Salim Salim (JURNAL TEMATIK, 2019)
This study aims to know the effect of life pharmacies on the introduction of science in children aged 5-6 years old at TK Aisyiyah BustanulAthfal 06 Bromo Medan. This research uses a quantitative approach with an experimental research design. The design in this study was Pre-Experimental Designs, in the form of One-Group PretestPostest Design. The sampling technique is done by random sampling, namely by selecting samples by random method, because the population has the same characteristics in terms of age, namely 5-6 years of age. Data collection techniques by observing with the observation guide instrument. Data analysis with descriptive statistics and t-test to test hypotheses. The results of the analysis show (posttest) that utilizes a better pharmacy / higher compared to the control class. The highest score was in the posttest 14 data, whereas in the 12th pretest. Posttest data averages 10.1, for pretest data 7.5. Based on these results it states that a live pharmacy provides a significant influence on the introduction of children's science that is from the results of hypothesis testing obtained t count = 18.57> t table = 1.729. This shows that there is a significant influence of life pharmacies on the introduction of science of children aged 5-6 in Kindergarten Aisyiyah Bustanul Athfal 06 Bromo Medan.